The Influence of Personality Traits and Domain Knowledge on the Quality of Decision-Making in Engineering Design - Muhammad Ahmad; Guoxin Wang (Applied Sciences)
In engineering design, the decision-making process holds significant importance as it plays an important role in determining the outcomes of a task. The decision-making process is notably influenced by various factors, with particular focus on the personality traits and information available. The purpose of this study is to comprehensively investigate the effects of these factors on quality and confidence in decision-making within the context of engineering design. To achieve this objective, we utilized a simulated design environment that can capture decision-making information. The analysis of personality traits was carried out utilizing the complete Big Five model, while the estimate of the structural equation model was executed by employing partial least squares structural equation modeling (PLS-SEM) and a machine learning model for quality estimation. The available empirical research indicates that individuals who have a lower degree of extraversion and agreeableness, and higher levels of conscientiousness and openness, are more likely to make decisions of higher quality. These characteristics have been found to have no significant effect on the levels of confidence during the process of making decisions. Furthermore, it was found that the trait of neuroticism has a negative impact on the quality of decision-making but does not have a significant impact on decision-making confidence. The noticeable finding was the strong impact of test-assessed knowledge on decision quality and confidence, in contrast to the lack of significant effect of self-assessed knowledge. This highlights the importance of carefully aligning tasks with individual personality traits in organizations working in the engineering design sector and prioritizing factual demonstrated knowledge rather than subjective self-assessment when assigning decision-making positions to individuals. These findings highlight the importance of considering personality traits and domain knowledge in educational and professional settings to enhance decision-making quality and confidence among engineering students, potentially informing targeted training and assessment practices.